2011
DOI: 10.1891/0889-8391.25.3.218
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Defusion Versus Cognitive Restructuring in the Treatment of Negative Self-Referential Thoughts: An Investigation of Process and Outcome

Abstract: Within traditional cognitive therapy, cognitive restructuring is often used to challenge the veracity of dysfunctional thoughts. In contrast, acceptance and commitment therapy (ACT) uses "cognitive defusion" techniques to change the function of negative thoughts rather than modify their content. Previous research has shown that a cognitive defusion technique known as the "milk exercise" (rapidly repeating a self-referential, one-word thought such as "fat") reduces the discomfort and believability associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 18 publications
3
57
1
12
Order By: Relevance
“…CBT is a highly effective treatment for a wide range of mental [12,49]. Cognitive-behavioral researchers have also recognized that the assessment of positive and negative cognitions may contribute to a better understanding of psychopathology and the development of more effective treatments [43,50].…”
Section: Automatic Thought In Cognitive-behavioral Therapy (Cbt)mentioning
confidence: 99%
See 1 more Smart Citation
“…CBT is a highly effective treatment for a wide range of mental [12,49]. Cognitive-behavioral researchers have also recognized that the assessment of positive and negative cognitions may contribute to a better understanding of psychopathology and the development of more effective treatments [43,50].…”
Section: Automatic Thought In Cognitive-behavioral Therapy (Cbt)mentioning
confidence: 99%
“…Accordingly, a common technique in traditional cognitive-behavioral therapy (CBT) is cognitive restructuring [10]. The goal of this process is to encourage patients to think in more accurate and adaptive ways, which facilitate effective problem solving and living a more satisfying life [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…As such, the cognitive defusion condition reduced the emotional discomfort and believability of negative self-referential thoughts (Masuda et al, 2010 ). There are various techniques in psychotherapy such as deliteralization and physicalizing that creates space between thoughts and emotions, by disidentifying and disengaging from them (Deacon, Fawzy, Lickel, & Wolitzky-Taylor, 2011 ). Although a distinction is made between cognitive defusion and cognitive realignment/restructuring in terms of intention to change the contents of thoughts versus their function, MDT incorporates both in a systematic way depending on the nature and context of problematic thoughts.…”
Section: Cognitive Defusionmentioning
confidence: 99%
“…However, cognitive restructuring may only encourage attempts to suppress and avoid undesirable thoughts, while cognitive defusion practices awareness and acceptance, which defuses the power of thoughts without changing their contents. Deacon et al ( 2011 ) concluded that both cognitive defusion and cognitive restructuring produce reductions in negative self-referential thoughts, but that defusion has a more immediate effect while not always relating effectively in the longer term to real-life contexts, which seemed to relate to the believability of the negative thoughts. The notion of MDT is that thoughts that are defused, and therefore have no deep attachment or value, are easier to realign by way of healthier alternative beliefs.…”
Section: Cognitive Defusionmentioning
confidence: 99%
“…Rather than challenging the validity of the thoughts as is done in CBT, ACT changes the function of the thought, making it less emotionally salient. This can be done through cognitive defusion techniques such as decreasing the thought to one word (e.g., "I am fat" to "fat") and repeating the word out loud multiple times until the word loses its literal meaning (46). The goal is to have the patient realize that thoughts are not literal but rather just thoughts that have nothing to do with the quality of the person who is experiencing them (47).…”
Section: Acceptance and Commitment Therapymentioning
confidence: 99%